Pengaruh Pengetahuan Pasar Modal Syariah dan Kemudahan Akses Informasi Terhadap Minat Investasi Saham di Pasar Modal Syariah: Studi pada Mahasiswa di Bandar Lampung - Joko Suprianto; Any Eliza; Sherly Etika Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to determine the influence of Sharia Capital Market Knowledge and Information Accessibility on Interest in Stock Investment in the Sharia Capital Market among university students in Bandar Lampung, both partially and simultaneously, and reviewed from the perspective of Islamic Economics and Business. This study used a quantitative approach with a survey method. Primary data were collected through online questionnaires distributed to students who were familiar with or had used shariabased digital investment platforms. The data analysis techniques used included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results showed that Sharia Capital Market Knowledge had a positive and significant effect on Interest in Stock Investment in the Sharia Capital Market, with a t-value of 5.784 and a significance value of 0.001 < 0.05. Information Accessibility also had a positive and significant effect on Interest in Stock Investment in the Sharia Capital Market, with a t-value of 2.513 and a significance value of 0.014 < 0.05. Simultaneously, Sharia Capital Market Knowledge and Information Accessibility had a positive and significant effect on Interest in Stock Investment in the Sharia Capital Market, with an F-value of 57.178 greater than the F-table value of 3.091 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) value of 0.549 indicates that the two independent variables were able to explain 54.9% of the variation in investment interest. From the perspective of Islamic Economics and Business, sharia investment represents a form of wealth management carried out in a lawful, transparent manner and in accordance with sharia principles.